Taklukkan matematika dengan self-regulated learning: Strategi untuk belajar mandiri dan efektif - Turrohmah, Laili Fayzza (Maliki Interdisciplinary Journal, 2024)
Mathematics is often a nightmare for many students. Fear and lack of self-confidence can hinder the learning process and achievement. This research aims to thoroughly examine self-regulated learning (SRL) strategies that are effective in improving the ability to learn mathematics independently and efficiently.SRL is defined as an individual’s ability to organize and control their own learning process. The application of SRL in learning mathematics can help students set goals, choose appropriate learning strategies, monitor learning progress, and evaluate learning outcomes. This research describes effective strategies with SRL that can be applied in learning mathematics. The findings of this research indicate that implementing appropriate SRL strategies can help students learn mathematics independently and effectively, increase self-confidence, and achieve better achievement.